Romanla Kimlikleşen Bir Yüz: Halide Edib Adıvar ve Edebi Yaratımları - Şahin, Veysel (Karamanoğlu Mehmetbey Üniversitesi, 2018)
Son devir Türk edebiyatında önemli bir yere sahip olan Halide Edib Adıvar, Türkiye’nin imparatorluktan cumhuriyete geçiş sürecinde, Türk insanı ve toplumunun yaşadığı değişim ve dönüşümleri kendi benliğinde yaşamış ve bunları da yazdığı metinlere taşımış, modern bir kadın, düşün ve eylem insanıdır. Yaşadığı devre ve tarihi köklere, kopmaz bir bağ ile bağlı olan yazar, dönem ve edebî eser arasındaki çift yönlü ilişkiyi güçlü bir seziş, okuma ve gözlemleriyle eserlerine yansıtır. Yazın hayatına yirmi bir roman, dört hikâye kitabı, iki tiyatro, onlarca çeviri, yüzlerce fikir yazısı, yedi inceleme kitabı ve üç anı kitabı sığdıran Adıvar, yaşadığı döneme gerek kişiliği gerekse eserleriyle damga vurur. Cumhuriyet Dönemi Türk romanının önde gelen isimleri arasında yer alan Halide Edib Adıvar’ın romanları, yapı ve izleksel kurgusu açısından “Bireysel ve Psikolojik İzlekli Romanlar, Yeniden Kuruluş ve Kurtuluş Savaşı İzlekli Romanlar ve Töre ve Toplumsal İzlekli Romanlar,” olmak üzere temel üç ana başlığa ayrılır.

Halide Edib Adıvar, having an important position in the recent Turkish literature, has experienced the change and the conversion of Turkish people and society in her own life in Turkey’s transition process from the Empire into the Republic and she has narrated these situations abovementioned. Also, she is the modern, intellectual woman and the person of action. The author, who has adhered both to the period in which she lived and to the historical roots, projects the bi-directional relationship between the period and the literary works into her creations with a strong intuition, observation and reading. Adıvar, who has produced twenty one novels, four story books, two plays, over ten translations, over one hundred essays, seven reviews and three memoirs during her writing career, leaves her mark in her period with both her personality and her works.               The novels of Halide Edib Adıvar, who is one of the prominent figures in Republican Period Turkish novel, are distinguished into three in terms of structure and thematic patterning: Psychology and Individual themed novels, Re-establishment and War of Independence themed novels, Manners and Societal themed novels.
A Face With Roman: Halide Edib Adıvar and Literature Creations
Keywords: Creative Arts and Writing; Sanat ve Edebiyat